كثافة الحجاج البلاغي في مقال الكواكبي "الاستبداد والعلم" دراسة تطبيقية - سعداني, الأخضر (جامعة الوادي - university of Eloued, 2022)
يعرض هذا البحث تحليلا للحجاج البلاغي في مقال للأديب عبد الرحمن الكواكبي موسوم بـ"الاستبداد والعلم". حلل فيه الكاتب طبيعة المستبد وموقفه من تعليم المحكومين، وصور فيه نفسية الحاكم في علاقته بالعلماء وبحاشيته ، ساعيا إلى نتيجة رئيسية هي: لا تعايش بين وجود الاستبداد والعلم. وتمثل هذه المداخلة إجابة عن الاشكالية التالية: كيف استعمل الكواكبي التقنيات البلاغية في حجاجه ضد المستبد؟ وهل كان ماهرا في فضح طبائع الاستبداد، قادرا على إثارة جماهيره المتلقية، نافثا في نفوسهم قبول الأفكار التي يؤمن بها هو نفسه ويعمل في الواقع على تجسيدها؟ This research presents an analysis of the rhetorical pilgrims in an article by the writer Abd al-Rahman al-Kawakibi, tagged with "tyranny and science". In it, the writer analyzed the nature of the tyrant and his position on the education of the governed, and depicted the psychology of the ruler in his relationship with scholars and his entourage, seeking a main conclusion: there is no coexistence between the existence of tyranny and science. This intervention represents an answer to the following problem: How did al-Kawakibi use rhetorical techniques in his arguments against the tyrant? Was he skillful in exposing the nature of tyranny, able to excite his audience, inspiring in their hearts to accept the ideas in which he himself believes and is actually working to embody them?
مقال
Keywords: الحجاج, التشبيه التمثيلي، الإقناع، الحجة، النتيجة، الكواكبي; arguments, analogy, persuasion, argument, conclusion, al-Kawakibi